To Label or Not? Governing the Costs and Benefits of Geographic Indication of an African Forest Honey Value Chain - Ingram, Verina; Hansen, Maria Ellemann; Bosselmann, Aske Skovmand (Frontiers in Forests and Global Change, 2020)
Geographical Indication (GI) has been proposed as a development tool, benefitting producers, consumers and local communities by creating value, improving market access, protecting local knowledge and natural resources and contributing to social cohesion as producers work together to solve common problems. However, scientific evidence on the socio-economic and environmental effects of governing value chains and origin landscapes through this voluntary, market-based arrangement is scarce. Honey appears ideal for GI labelling: having unique, physically identifiable and geographically localisable properties dependent upon the local ecosystem and beekeeping practices. White honey from the Kilum-Ijim forest in the Cameroon Highlands was GI registered in 2013 aiming to guarantee product quality, increase beekeeper selling prices and protect the forest. Panel data from stakeholder interviews, market surveys and participatory action research, shows the extent to which the GI benefited beekeepers, and how the honey value chain and landscape developed since registration. Although honey production and productivity remained steady, profits augmented as prices increased and sales became more nationwide, improving beekeeper’s living standards, appearing attributable to the GI. Deforestation however continued, and imposter brands abound, signalling potential supply shortages, increased input costs and competition which could affect future profits and the GI reputation; changing the distribution of benefits to suppliers rather than beekeepers. This suggests that whilst the Oku white honey GI has had a short-term positive livelihood effects, longer-term positive impacts conserving the landscape have been ineffective, and the durability of economic impacts is questionable. Although multiple arrangements govern the value chain and landscape, even together they are insufficient to balance the many demands on this productive landscape, suggesting the limits of weak institutions and non-state governance to protect vulnerable landscapes and ecosystems, and producer’s livelihoods. This reality check of the benefits from the Oku white honey GI highlights the importance of coherent, effective governance of both landscapes and the markets for its products.